2017
DOI: 10.1007/s00424-017-1962-6
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological blockade of small conductance Ca2+-activated K+ channels by ICA reduces arrhythmic load in rats with acute myocardial infarction

Abstract: Acute myocardial infarction (AMI) with development of ventricular fibrillation (VF) is a common cause of sudden cardiac death (SCD). At present, no pharmacological treatment has successfully been able to prevent VF in the acute stage of AMI. This study investigates the antiarrhythmic effect of inhibiting small conductance Ca-activated K (SK) channels using the pore blocker N-(pyridin-2-yl)-4-(pyridin-2-yl)thiazol-2-amine (ICA) in AMI rats. Acute coronary ligation was performed in 26 anesthetized rats, and ECG,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…As SK channels appears to play a role in some pathological conditions in the ventricles (Gui ; Bonilla ; Hundahl ; Chen ; Hamilton ), it could be speculated that the SK channels also have a contributory role in the pathogenesis of CaM‐associated LQTS. Three out of the four LQTS‐associated CaM variants significantly down‐regulated the SK current, with CaM D130G being the variant most profoundly decreasing SK current with no effect on the trafficking of the channel.…”
Section: Discussionmentioning
confidence: 99%
“…As SK channels appears to play a role in some pathological conditions in the ventricles (Gui ; Bonilla ; Hundahl ; Chen ; Hamilton ), it could be speculated that the SK channels also have a contributory role in the pathogenesis of CaM‐associated LQTS. Three out of the four LQTS‐associated CaM variants significantly down‐regulated the SK current, with CaM D130G being the variant most profoundly decreasing SK current with no effect on the trafficking of the channel.…”
Section: Discussionmentioning
confidence: 99%
“…Under these conditions, some studies have shown that ventricular small-conductance Ca2+-activated K+ current can be upregulated and that blocking small-conductance Ca2+activated K+ current can exhibit both proarrhythmic 17,18 and antiarrhythmic. [19][20][21] In addition, preclinical experiments with AP30663 yielded conflicting results. In an in vitro experiment, no effect of AP30663 on the ventricular interval was observed at a concentration of 30 µM (estimated concentration: 12,000 ng/mL).…”
Section: Ventricular Effects Of K Ca 2 Channel Inhibitionmentioning
confidence: 99%
“…In a pacing-induced rat AF model, intravenous application of NS8593, a highly selective SK channels blocker, reduced the duration of AF by 64.5% [ 9 ]. Pharmacological blockade of SK channels with the pore blocker ICA in acute myocardial infarction with development of ventricular fibrillation (VF) significantly decreased VT duration and returned monophasic action potential duration at 80% repolarization (MAPD80) to baseline [ 10 ]. Hsueh et al demonstrated that SK channel blockade promoted arrhythmias in the canine left atrium, which could be attributed to the increase in APD heterogeneity [ 11 ].…”
Section: Introductionmentioning
confidence: 99%